Multinational firms, FDI flows and imperfect capital markets - Antràs, Pol 1975-; Desai, Mihir A. 1968-; Foley, C. Fritz (Working paper series / National Bureau of Economic Research, 2007)
This paper examines how costly financial contracting and weak investor protection influence the cross-border operational, financing and investment decisions of firms. We develop a model in which product developers have a comparative advantage in monitoring the deployment of their technology abroad. The paper demonstrates that when firms want to exploit technologies abroad, multinational firm (MNC) activity and foreign direct investment (FDI) flows arise endogenously when monitoring is nonverifiable and financial frictions exist. The mechanism generating MNC activity is not the risk of technological expropriation by local partners but the demands of external funders who require MNC participation to ensure value maximization by local entrepreneurs. The model demonstrates that weak investor protections limit the scale of multinational firm activity, increase the reliance on FDI flows and alter the decision to deploy technology through FDI as opposed to arm's length licensing. Several distinctive predictions for the impact of weak investor protection on MNC activity and FDI flows are tested and confirmed using firm-level data.